Spiritualities and social dynamics: memory and perspectives - A review for the 27th SOTER Congress - Mariani, Ceci Maria Costa Baptista (2014)
This is a communication regarding the 27th congress of the Society of Theology and Religious Studies (SOTER), held between the 15th and 18th of July, 2014. According to the proposition established by 2013’s assembly, the Congress assumed as common thread the relationship between spiritualties and social dynamics and also offered a debate about spirituality as endurance in times of oppression. This review highlights some topics that brought up important provocations, considering a needful depth, in order to think of new perspectives in the context of the connection between religion and society.